Respuesta :

Answer:

-(8/-4)² + 2 - 4³ = -66

Step-by-step explanation:

-(8/-4)² + 2 - 4³

Here we need to respect the order of operations.

So ,first we calculate what’s between parentheses :

8/-4 = -2

Then

-(8/-4)² + 2 - 4³ = -(-2)² + 2 - 4³

Then

We calculate the exponent :

(-2)² = (-2) × (-2) = 4

4³ = 4 × 4 × 4 = 64

Then

-(8/-4)² + 2 - 4³ = -4 + 2 - 64

Then

The expression -4 + 2 - 64 contains addition and subtraction.

So ,we start calculating from left to right :

-4 + 2 = -2

Then

-4 + 2 - 64 = -2 - 64 = -66

Conclusion :

-(8/-4)² + 2 - 4³ = -66